The relationship between the gap of knowledge and the strategic performance gap - كريم, صلاح الدين عواد (Journal of Economics and Administrative Sciences, 2012)
Address the intellectual controversy nature of the gap of knowledge and the strategic performance gap. The researcher start off from this intellectual controversy to seek to test the nature of the relationship and impact between them across a sample of (61) academics in the colleges of business and economics at the universities in Baghdad ,as the more specialized in the fields of knowledge and the strategic performance, The researcher is attain to the existence of relationship and impact of knowledge gap in strategic performance gap, the research included four axes first went to the methodology and second to theoretical frame and the third to view and analyze the results and test hypotheses while the fourth was devoted to the conclusions and recommendations.